2020
DOI: 10.1038/s41598-020-70612-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term manure nitrogen input on soil microbial community structure and diversity in a double-cropping paddy field of southern China

Abstract: The soil physicochemical properties and soil microbial communities were affected by different fertilizer management. Fertilizer regime were closely relative to the soil texture and nutrient status in a doublecropping paddy field of southern China. However, there was limited information about the influence of different manure nitrogen (N) input on soil microbial communities in a double-cropping rice (Oryza sativa L.) field. Therefore, the short-term different manure N input rate management on soil bacterial and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 36 publications
3
33
2
1
Order By: Relevance
“…The oil palm plantation soil is mainly dominated in the order by Acidobacteria > Proteobacteria > Actinobacteria > Firmicutes > Bacteroidetes > Chloroflexi whereas the order was Firmicutes > Bacteroidetes > Chloroflexi > Planctomycetes for secondary forest. The results are comparable to the previous studies, which showed that soil in oil palm plantation is dominated mostly by all of these bacterial phyla (Lee-Cruz et al 2013;Berkelmann et al 2020;Tang et al 2020). The results showed that long term continuous cropping decreased the Bacteroides and Firmicutes phyla of the oil palm plantation.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The oil palm plantation soil is mainly dominated in the order by Acidobacteria > Proteobacteria > Actinobacteria > Firmicutes > Bacteroidetes > Chloroflexi whereas the order was Firmicutes > Bacteroidetes > Chloroflexi > Planctomycetes for secondary forest. The results are comparable to the previous studies, which showed that soil in oil palm plantation is dominated mostly by all of these bacterial phyla (Lee-Cruz et al 2013;Berkelmann et al 2020;Tang et al 2020). The results showed that long term continuous cropping decreased the Bacteroides and Firmicutes phyla of the oil palm plantation.…”
Section: Resultssupporting
confidence: 87%
“…3). Soil physicochemical properties and microbial community structure are mainly affected by different fertilizer management, as indicated by Tang et al (2020), whereby the application of organic and inorganic fertilizer significantly alter the soil microbial diversity and activities of the paddy field. The three-dimensional principal coordinates analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Basidiomycota and Glomeromycota accounting the greatest dissimilarity in Org_M compared with conventional cropping system and previous studies showed Basidiomycota, which are the main decomposer of plant litter [79] was increase in soils with manure since it provide an appropriate environment for Basidiomycota [80] However, chemical fertilizer can cause the loss of that environment and hinder the development of this phyla [80]. High abundance of Glomeromycota in Org_M can form arbuscular my-corrhiza with plants and absorb nutrients directly, particularly P uptake of plant roots [81], promoting plant growth, and enhances plant resistance to various pathogens [82], so it could be possible that its high abundance is related to the lower abundance of both pathogens Fusarium oxysporum and Alternaria spp.…”
Section: Discussionmentioning
confidence: 98%
“…Basidiomycota and Glomeromycota had the greatest dissimilarity in Org_M compared with Conv. Previous studies showed that Basidiomycota was increased in soils with manure as it provides an appropriate environment for Basidiomycota [76]. However, chemical fertilizer can cause the loss of that environment and can hinder the development of this phyla [76].…”
Section: Discussionmentioning
confidence: 99%